Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1542/peds.2013-0911
|View full text |Cite
|
Sign up to set email alerts
|

Screening Strategies for Hip Dysplasia: Long-term Outcome of a Randomized Controlled Trial

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Only 2 randomized controlled trials have addressed effects of ultrasound screening for developmental hip dysplasia. Both concluded that adding universal or selective ultrasound to routine clinical examination gave a nonsignificant reduction in rates of late presenting cases, but higher treatment rates. WHAT THIS STUDY ADDS:This maturity review assesses long-term outcome of one of these trials. Rates of radiographic findings indicating acetabular dysplasia and degenerative change w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 44 publications
0
39
0
2
Order By: Relevance
“…However, it was reported that the majority of patients in the United States with symptomatic dysplasia of the acetabulum at skeletal maturity do not meet the criteria for selective ultrasound screening [61] . Recently, a large randomized controlled study comparing universal or selective ultrasound screening with well performed physical examination showed higher treatment rates, a slight reduction in late diagnosis of dysplasia which was not significant, and increased treatment rates which were not associated with AVN [62] . A Cochrane review of screening programs for DDH in newborns found that studies that compared the addition of ultrasonography to clinical examination reported that, when ultrasonography was performed on all infants, the rate of treatment increased with no significant change in the rate of late detected dysplasia or surgery.…”
Section: Ultrasonographymentioning
confidence: 99%
“…However, it was reported that the majority of patients in the United States with symptomatic dysplasia of the acetabulum at skeletal maturity do not meet the criteria for selective ultrasound screening [61] . Recently, a large randomized controlled study comparing universal or selective ultrasound screening with well performed physical examination showed higher treatment rates, a slight reduction in late diagnosis of dysplasia which was not significant, and increased treatment rates which were not associated with AVN [62] . A Cochrane review of screening programs for DDH in newborns found that studies that compared the addition of ultrasonography to clinical examination reported that, when ultrasonography was performed on all infants, the rate of treatment increased with no significant change in the rate of late detected dysplasia or surgery.…”
Section: Ultrasonographymentioning
confidence: 99%
“…37 The USPSTF also raised concerns about the psychological consequences or stresses with early diagnosis and intervention. Gardner et al 38 found that the use of hip ultrasonography allowed for reduction of treatment rates without adverse clinical or psychological outcomes.…”
Section: Screening and Diagnosismentioning
confidence: 99%
“…33 Other studies have reported much lower rates of AVN. 36,37 One prospective study reported a zero prevalence of AVN by 6 years of age in mildly dysplastic hips treated with bracing. 30 However, abduction brace treatment is not innocuous.…”
Section: Risks Of Treatmentmentioning
confidence: 99%
“…One characteristic physical examination finding is a lack of passive external rotation of the shoulder, but it is likely that physical examination alone will miss some dislocations. There is a strong precedent for targeted ultrasound screening of infants at risk for developmental hip dysplasia, making ultrasound a natural choice for screening for glenohumeral joint dysplasia in infants with BPBP 5,6 . The technique of shoulder ultrasound in BPBP has been well-described, but which infants with BPBP should undergo ultrasound screening is not yet understood 7 .…”
mentioning
confidence: 99%